Roasting Degree as a Design Lever: Physicochemical Quality, Sensory Appeal, and Youth Preference in Hot-Process Upcycled Robusta Coffee Soap - Wulandari, Sri; Sidik, Gusmon; Anggraini, Septiana; Ikarini, Imro'ah; Yustina, Ita (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2025)
AbstractDemand for natural solid soaps is rising due to skin safety and sustainability concerns. Robusta coffee contains pigments and bioactive compounds whose properties vary with roasting degree and may affect soap quality. This study evaluated the effects of light, medium, and dark roasting on the physicochemical characteristics of natural coffee soap and young consumer preferences. Soaps were produced using a heat process in a completely randomized design with three replications. Analyses included moisture content, pH, free fatty acids, free alkalis, caffeine content, and color, while a hedonic test involving 199 panelists aged 16–24 assessed color, aroma, and overall appearance. Coffee samples showed water content of 3.40–5.20%, pH 5.92–6.81, and caffeine 1.63–1.77%. Soap water content ranged from 10.71–14.61%, pH 10.29–10.60, free fatty acids 0.66–1.22%, free alkalis 0.25–0.34%, and caffeine 0.20–0.24 mg g⁻¹. Roasting degree did not affect free alkalis. Dark-roasted coffee soap received the highest aroma and overall appearance scores, while color preference did not differ significantly. These results support the development of dark-roasted coffee soap for young consumers and highlight the need to optimize the oil-to-NaOH ratio to meet Indonesian National Standards and support circular economy-based value-added products.Keywords: Consumer preference, natural coffee soap, physicochemical quality, roast degree, Robusta coffee AbstrakPermintaan sabun mandi padat berbahan alami meningkat seiring perhatian terhadap keamanan kulit dan keberlanjutan. Kopi Robusta menawarkan pigmen dan senyawa bioaktif yang dipengaruhi derajat sangrai sehingga berpotensi mengubah mutu sabun. Penelitian ini bertujuan mengevaluasi pengaruh sangrai ringan, sedang, dan gelap terhadap karakteristik fisikokimia sabun kopi alami dan preferensi konsumen muda. Pembuatan sabun dilakukan melalui proses panas menggunakan rancangan acak lengkap, 3 ulangan setiap perlakuan. Parameter yang dianalisis meliputi kadar air, pH, asam lemak bebas, alkali bebas, kadar kafein, dan karakter warna. Uji hedonik melibatkan 199 panelis berusia 16–24 tahun yang menilai warna, aroma, dan penampilan keseluruhan. Kadar air kopi berada pada 3,40–5,20%, pH 5,92–6,81, dan kafein 1,63–1,77%. Sabun menunjukkan kadar air 10,71–14,61%, pH 10,29–10,60, asam lemak bebas 0,66–1,22%, alkali bebas 0,25–0,34%, dan kafein 0,20–0,24 miligram per gram. Sangrai tidak memengaruhi alkali bebas. Sabun sangrai gelap memperoleh skor aroma dan penampilan keseluruhan tertinggi, sedangkan skor warna tidak berbeda nyata. Temuan ini mendukung pengembangan sabun kopi alami berbasis sangrai gelap bagi segmen konsumen muda, dan menekankan kebutuhan optimasi rasio minyak terhadap NaOH agar alkali bebas memenuhi Standar Nasional Indonesia dan siap dikembangkan sebagai produk bernilai tambah yang mendukung ekonomi sirkular.Kata kunci: Derajat sangrai, kopi Robusta, mutu fisikokimia, preferensi konsumen, sabun kopi alami